Beyond PD-1 Immunotherapy in Malignant Melanoma - Dominika Kwiatkowska; Piotr Kluska; Adam Reich (Adis, Springer Healthcare, 2019)
Abstract For many years, the standard therapy for malignant melanoma was based mainly on surgical resection. Unfortunately, this treatment is curative only in the early localized stage of this malignancy. The metastatic stage of malignant melanoma still remains a huge therapeutic challenge. Despite the many new therapeutic options that have become available over the last years, there is a constant need for safer and more effective treatment modalities. There has been a dynamic development of various anti-cancer immunotherapies directed against new molecular targets. A number of clinical trials are currently being conducted to confirm their effectiveness and safety. In this review of the literature, we summarize the contemporary knowledge on promising new immunotherapies beyond the currently available treatment options for malignant melanoma, including oncolytic immunotherapy, selective inhibitors of indoleamine 2,3-dioxygenease, anti-PD-(L)1 (programmed death ligand 1) drugs, immune checkpoint protein LAG-3 antibodies, inhibitors of histone deacetylase (HDAC) and inhibitors of B7-H3.